La déclaration de la victime au tribunal : évaluation de l’expérience du Palais de Justice de Montréal - Laflamme-Cusson, Suzanne (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1990)
In October 1987, an experimental program was introduced in the Montreal Law Courts, inviting victims of crime and personal attack, as well as victims of burglary, to inform the Court of the consequences they suffered because of these acts; the program was called the Déclaration de la victime. An evaluative study of this experiment was initiated at the same time. The article presents some results : the response of the victims when offered the opportunity of taking part in the judicial debate, the content of the declarations, their use by the members of the Court, their possible influence on the proceedings and on the judicial decisions.